2018
DOI: 10.18632/oncotarget.25697
|View full text |Cite
|
Sign up to set email alerts
|

Patient derived renal cell carcinoma xenografts exhibit distinct sensitivity patterns in response to antiangiogenic therapy and constitute a suitable tool for biomarker development

Abstract: Systemic treatment is necessary for one third of patients with renal cell carcinoma. No valid biomarker is currently available to tailor personalized therapy. In this study we established a representative panel of patient derived xenograft (PDX) mouse models from patients with renal cell carcinomas and determined serum levels of high mobility group B1 (HMGB1) protein under treatment with sunitinib, pazopanib, sorafenib, axitinib, temsirolimus and bevacizumab. Serum HMGB1 levels were significantly higher in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…In translational applications, panels of PDX models can screen for drug efficacy, resistance mechanisms, and aid in identifying biomarkers of predictive of drug sensitivity and response (Table 1). In a large cohort of mice grafted from a heterogeneous population of patient RCC tumors, Schueler et al found that they were able to predict tumor response to therapy based on HMGB1 levels [50]. Traditional systemic chemotherapies have been notoriously ineffective against advanced renal cell carcinoma.…”
Section: Correlation With Therapy Response and Chemosensitivitymentioning
confidence: 99%
“…In translational applications, panels of PDX models can screen for drug efficacy, resistance mechanisms, and aid in identifying biomarkers of predictive of drug sensitivity and response (Table 1). In a large cohort of mice grafted from a heterogeneous population of patient RCC tumors, Schueler et al found that they were able to predict tumor response to therapy based on HMGB1 levels [50]. Traditional systemic chemotherapies have been notoriously ineffective against advanced renal cell carcinoma.…”
Section: Correlation With Therapy Response and Chemosensitivitymentioning
confidence: 99%
“…Existing and new PDX models brought onto the market are, however, often fully characterized in terms of mutational and transcriptomic status, growth rate, differentiation, vascularization, amount of stroma content, etc. which allow this wealth of information for each model to be exploited for understanding the specific traits of patient tumors that could be successfully targeted [ 9 ], and thereby give valuable insights for designing clinical trials [ 8 ]. As such, PDX models provide a better foundation for drug development and basic cancer research compared to fresh patient tumor samples.…”
Section: Discussionmentioning
confidence: 99%
“…Only the Vhldel Ink4a/Arf-del model produced some metastasis, but only in the liver. However, no suitable GEMMs of RCC recapitulating with high fidelity the metastatic process, as our model does, exists to date [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%